Potentially inappropriate medication including drug-drug interaction and the risk of frequent falling, hospital admission, and death in older adults - results of a large cohort study (getABI) - Theresa Reinhild Haerig; Dietmar Krause; Renate Klaassen-Mielke; Henrik Rudolf; Hans Joachim Trampisch; Petra Thuermann (Frontiers Media S.A., 2023)
Introduction: With growing age, multiple chronic diseases may result in polypharmacy. Drugs that should be avoided in older adults are called potentially inappropriate medications (PIM). Beyond PIM, drug-drug interactions (DDI) are known to be related to adverse drug events. This analysis examines the risk of frequent falling, hospital admission, and death in older adults associated with PIM and/or DDI (PIM/DDI) prescription.Materials and methods: This post hoc analysis used data of a subgroup of the getABI study participants, a large cohort of community-dwelling older adults. The subgroup comprised 2120 participants who provided a detailed medication report by telephone interview at the 5-year getABI follow-up. The risks of frequent falling, hospital admission, and death in the course of the following 2 years were analysed by logistic regression in uni- and multivariable models with adjustment for established risk factors.Results: Data of all 2,120 participants was available for the analysis of the endpoint death, of 1,799 participants for hospital admission, and of 1,349 participants for frequent falling. The multivariable models showed an association of PIM/DDI prescription with frequent falling (odds ratio (OR) 1.66, 95% confidence interval (CI) 1.06-2.60, p = 0.027) as well as with hospital admission (OR 1.29, 95% CI 1.04-1.58, p = 0.018), but not with death (OR 1.00, 95% CI 0.58-1.72, p = 0.999).Conclusion: PIM/DDI prescription was associated with the risk of hospital admission and frequent falling. No association was found with death by 2 years. This result should alert physicians to provide a closer look at PIM/DDI prescriptions.